Bayesian mixture modelling for mortality projection - Jackie Li; Atsuyuki Kogure (Risks, 2021)
Although a large number of mortality projection models have been proposed in the literature, relatively little attention has been paid to a formal assessment of the effect of model uncertainty. In this paper, we construct a Bayesian framework for embedding more than one mortality projection model and utilise the finite mixture model concept to allow for the blending of model structures. Under this framework, the varying features of different model structures can be exploited jointly and coherently to have a more detailed description of the underlying mortality patterns. We show that the proposed Bayesian approach performs well in fitting and forecasting Japanese mortality.
Keywords: 330; age-cohort model; Bayesian modelling; Cairns-Blade-Dowd model; finite mixture model; Lee-Carter model